GENETIC VARIATIONS OF TWO Anguilla SPECIES IN THE WEST COAST OF WEST SUMATRA AND MENTAWAI USING RAPD - Syaifullah syaifullah; Annisya Fitri; Djong Hon Tjong; Dewi Imelda Roesma; Indra Junaidi Zakaria (Jurnal Biologi Universitas Andalas, 2023)
Research on the genetic variation of Anguilla spp. in the waters of the West Coast of West Sumatra was carried out from February to June 2022. This study used the RAPD (random amplified polymorphic DNA) method. In this study, two Anguilla species were found, namely A. marmorata and A. bicolor bicolor. The highest heterozygosity value of A. marmorata in the Tarusan River was 0,2018, and A. bicolor bicolor in Mentawai was 0,2340. The values of gene flow (Nm) in A. marmorata and A. bicolor bicolor were 0.7592 and 1.6318. The values of genetic differentiation (GST) in A. marmorata and A. bicolor bicolor were 0.3971 and 0.2345, respectively. This shows that the value of genetic variation of A. marmorata and A. bicolor bicolor in several rivers on the west coast of West Sumatra is low.